Impact of Silymarin enriched semen extender on bull sperm preservability - R I El-Sheshtawy; W S El-Nattat (Asian Pacific Journal of Reproduction, 2017)
Objective: To explore the effect of silymarin on bull spermatozoa during cooling and cryopreservation.Methods: Pooled bull semen were diluted by Tris-Citrate-Fructose egg yolk diluents, purified silymarin powder (obtained from the milk thistle silybum marianum), purchased from Unipharma, Al Obour city, Egypt, was soaked in Tris-citric acid-fructose diluent for 48 h at 10 °C making a stock solution (70 mg/mL), from this stock solution we obtained concentrations of 0.18 mg/mL, 0.36 mg/mL, 0.54 mg/mL, 0.72 mg/mL, 0.90 mg/mL in addition to the control (0.00 mg/mL) reaching a final volume of 5 mL in each tube. Egg yolk was added to each tube to obtain silymarin enriched semen extender (SEE) with 20% egg yolk, cooled slowly up to 5 °C and equilibrated for 4 h. Semen was packed into 0.25 mL polyvinyl French straws (IMV, France). After equilibration periods, the straws were placed horizontally on a rack and frozen in a vapor 4 cm above liquid nitrogen for 10 min and were then dipped in liquid nitrogen. Extended semen was subjected to evaluation (motility, alive%, abnormality%, intact sperm membrane (HOST)% and conception rate) in both chilled and frozen semen.Results: [Table 1] revealed that Sperm motility of the concentrations 2, 3 and 4 after 8 d of chilling were significantly (P<0.02) higher than control. Sperm motility of the concentration 2 (45.00%±2.89%) after 9 d of chilling was higher than control and the other concentrations. Addition of SEE in concentration 1 and 2 gave post thawing sperm motility as high as the control (47.50±2.81 and 45.00±2.58, respectively) while other concentration have lower effects on motility as compared to the control. Addition of silymarin improved post thawing alive% and was significantly higher (P<0.000 1) than the control. SEE decreased significantly (P<0.000 1) the % of post thawing abnormal sperm in concentration 3 and 4 (11.83±0.65 and 16.00±0.58, respectively). SEE improved significantly (P<0.018) the % of post thawing intact spermatozoa membranes (HOST%) in concentrations 2, 4 and 5 (71.17±0.83, 71.83±0.91 and 75.00±3.42, respectively) [Table 2].Conclusion: It could be concluded that silymarin as a natural additive to semen extenders improved preservability in both chilled and frozen bull semen.